SELECTION OF SCHEMES AND CALCULATION OF FUNCTIONAL CHARACTERISTICS OF HYDROSTATIC TRANSMISSIONS FOR MOBILE MACHINES - O. V. Brilevski; A. P. Stezko; V. S. Shevchenko (Наука и техника)
The paper shows how to calculate hydraulic transmission of a loader and obtain its tractive characteristics. Practical recommendations for selection of a combination of hydraulic machines with hydrostatic transmissions are given in the paper.